Chemotaxis in Rhodobacter sphaeroides requires an atypical histidine protein kinase. - Porter, S; Armitage, J (2004)
Rhodobacter sphaeroides has a complex chemosensory system comprising two classic CheAs, two atypical CheAs, and eight response regulators (six CheYs and two CheBs). The classic CheAs, CheA(1) and CheA(2), have similar domain structures to Escherichia coli CheA, whereas the atypical CheAs, CheA(3) and CheA(4), lack some of the domains found in E. coli CheA. CheA(2), CheA(3), and CheA(4) are all essential for chemotaxis. Here we demonstrate that CheA(3) and CheA(4) are both unable to undergo ATP-dependent autophosphorylation, however, CheA(4) is able to phosphorylate CheA(3). The in vitro kinetics of this phosphorylation reaction were consistent with a reaction mechanism in which CheA(3) associates with a CheA(4) dimer forming a complex, CheA(3)A(4). To the best of our knowledge, CheA(3)A(4) is the first characterized histidine protein kinase where the subunits are encoded by distinct genes. Selective phosphotransfer was observed from CheA(3)-P to the response regulators CheY(1), CheY(6), and CheB(2). Using phosphorylation site and kinase domain mutants of CheA we show that phosphosignaling involving CheA(2), CheA(3), and CheA(4) is essential for chemotaxis in R. sphaeroides. Interestingly, CheA(3) was not phosphorylated in vitro by CheA(1) or CheA(2), although CheA(1) and CheA(2) mutants with defective kinase domains were phosphorylated by CheA(4). Because in vivo CheA(3) and CheA(4) localize to the cytoplasmic chemotaxis cluster, while CheA(2) localizes to the polar chemotaxis cluster, it is likely that the physical separation of CheA(2) and CheA(4) prevents unwanted cross-talk between these CheAs.